Puzzles about descriptive names - Kanterian, E (Springer, 2009)
This article explores Gareth Evans's idea that there are such things as descriptive names, i.e. referring expressions introduced by a definite description which have, unlike ordinary names, a descriptive content. Several ignored semantic and modal aspects of this idea are spelled out, including a hitherto little explored notion of rigidity, super-rigidity. The claim that descriptive names are (rigidified) descriptions, or abbreviations thereof, is rejected. It is then shown that Evans's theory leads to certain puzlles concerning the referential status of descriptive names and the evaluation of identity statements containing them. A tentative solution to these puzzles is suggested, which centres on the treatment of definite descriptions as referring expressions.